Investigating Students’ Engagement in ESP Online Course during Covid-19 Pandemic - Risa Arroyyani (Universitas Pahlawan Tuanku Tambusai, 2021)
This research aims to determine students’ engagement levels and factors in attending ESP online courses during the Covid-19 pandemic. In performing data and data analysis, a qualitative research design was employed with the interpretation of descriptive statistics. This research distributed a questionnaire to 59 students in the nursing department. The research findings showed that four dimensions of students’ engagements got a means score in the level of